Contract farming and everyday acts of resistance: Oil palm contract farmers in the Philippines - Caroline Hambloch (Journal of Agrarian Change, 2021)
Contract violations are critical issues determining the success and sustainability of contract farming (CF). This paper challenges the common portrayal of the “powerful” company versus the “powerless” landowners/smallholders by using the literature on labour agency in global value chains to understand minor contract violations of contract farmers such, as side-selling, refusal to harvest, and burning/felling of oil palm trees. This paper conceptualizes these violations as acts of minor agency or everyday acts of resistance. The analysis highlights how CF has created chains of dependency, in which smallholders are integrated into the modern market economy through new relations of debt and power. In response, contract farmers attempt to influence and shape the CF relation by using these different acts of minor agency. This paper finds that acts of minor agency, in the aggregate, can have important effects on contract relations, governance, and organizational structure of the chain and has the potential to lead to broader changes in the underlying social relations of contract. It highlights how individual acts of minor agency may contribute to the development of a consciousness of collective opposition to the contract relation.
Keywords: 630; agency; contract farming; oil palm; smallholders; value chains